2014
DOI: 10.2147/nrr.s36648
|View full text |Cite
|
Sign up to set email alerts
|

Practical implications for nurses caring for patients being treated for osteoporosis

Abstract: Osteoporosis is a major health problem throughout the world. Despite the serious consequences of osteoporosis and fractures, many people with low bone mass and those with osteoporosis are unaware of it, and as a result are not taking preventive actions and are receiving no treatment. Nurses have a major role in prevention, assessment, and teaching related to osteoporosis. This review presents what is currently known about osteoporosis and identifies specific activities that fall within the scope of nursing pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 103 publications
(113 reference statements)
0
2
0
Order By: Relevance
“…Fifty percent of patients become dependent on others after fractures that increase with age. It has been reported that the presence of fractures in more than one body part increases mortality (Smeltzer & Qi, 2014). With the impact of public health and increasing treatment costs, studies on the prevention of osteoporosis rather than treatment have gained weight all over the world (Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty percent of patients become dependent on others after fractures that increase with age. It has been reported that the presence of fractures in more than one body part increases mortality (Smeltzer & Qi, 2014). With the impact of public health and increasing treatment costs, studies on the prevention of osteoporosis rather than treatment have gained weight all over the world (Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Early diagnosis of osteoporosis risk factors and the development of effective prevention programmes are necessary to stop the progression of the disease. Nurses play an important role both in the prevention of osteoporosis and subsequent fractures in patients presenting with primary osteoporotic fractures (Fourie et al, 2015; Kalkim & Dağhan, 2017; Smeltzer & Qi, 2014). The health belief model (HBM) motivates individuals to acquire positive health behaviours and avoid negative ones (Kalkim & Dağhan, 2017; Kim et al, 2013).…”
Section: Introductionmentioning
confidence: 99%